Distributed storage system with solar photovoltaic energy source - Akkala, Kishore; Faranda, Roberto; Sodini, Pierfrancesco; Hafezi, Hossein (IEEE, 2019)
The management of Renewable Energy Sources (RES) and storage systems in order to connect to an LV distribution network imposes several challenges for the end-user. In addition, the nonlinear nature of the power electronic interfaces and the end-user loads create Power Quality issues in LV distribution network. In this paper, a power electronic device is proposed as a solution to the end-user for the management of RES, storage and for the mitigation of the Power Quality. The device, named Distributed Storage system, is connected in parallel to the end-user and the network. It facilitates online and island mode of operations. The device can manage injection of power into the network, of a RES, such as a PV, charging and discharging of a storage system and mitigate the Power Quality issues of the end-user by acting as a shunt active filter. The system structure, design, and control strategies are dealt with in this paper along with the description of hardware prototype realized.
Keywords: power quality; shunt active filter; solar photovoltaic RES; storage system; fi=Sähkötekniikka|en=Electrical Engineering|